Institutional entrepreneurship and change: The relevance of collective action - Pimentel, L.; Major, M. (35th EBES Conference - Program and Abstract Book, 2021)
Objectives: Drawing on the theoretical model of the process of entrepreneurship proposed by Battilana, Leca and Boxenbaum (2009), and on collective involvement/action literature, this paper aims to investigate how and why divergent institutional change was initiated by an individual institutional entrepreneur in a Portuguese government agency, where a new management model and new management control and accounting frameworks were implemented. Data and Methods: An in-depth and longitudinal explanatory study was carried out between January 2010 and March 2013. To this end, fifty-seven interviews were conducted and extensive documentation was analysed for the organization. Results: The investigation evidenced how an institutional entrepreneur could implement innovative management accounting frameworks. Findings also demonstrated that divergent change would not be possible without the back support of collective action. Moreover, evidence was found highlighting the relevance of factors such as actor’s organizational and structural capabilities, communication, cooperation, and motivation, not visualized in Battilana et al.’s (2009) model. Conclusions: The empirical study findings implied that a refined model of the process of entrepreneurship is proposed, highlighting collective action and other crucial additional factors and characteristics of the actors for the change process success. These are important contributions of the study. Originality/Contributions: The 33 originality and value of the research is seen in the proposition of a refined model of the process of entrepreneurship, highlighting the relevance of collective action to assure effectiveness in an institutional entrepreneurship process. The model of the process of institutional entrepreneurship and the role of collective action were empirically tested, implying that the model can be very useful to practitioners Keywords: Institutional Entrepreneurship, Institutional Change, Collective Action, Collective Institutional Entrepreneurship, Public Services